2014
DOI: 10.1088/0957-4484/25/50/504002
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis of highly ordered nanowires with a rectangular cross section using an in-plane nanochannel array

Abstract: Rapid and reproducible assembly of aligned nanostructures on a wafer-scale is a crucial, yet one of the most challenging tasks in the incorporation of nanowires into integrated circuits. We present the synthesis of a periodic nanochannel template designed for electrochemical growth of perfectly aligned, rectangular nanowires over large areas. The nanowires can be electrically contacted and characterized in situ using a pre-patterned multi-point measurement platform. During the measurement the wires remain with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Thus, there has not been global thinking about the names of DWs in these systems. Making this connexion is not a purely theoretical consideration, as processes are emerging for producing wires with a well-defined rectangular or square cross-section (Sergelius et al, 2014). Also, the latter should not be confused with the vortex wall in strips (McMichael and Donahue, 1997;Nakatani et al, 2005), which has a different shape and even topology, as we will detail later.…”
mentioning
confidence: 99%
“…Thus, there has not been global thinking about the names of DWs in these systems. Making this connexion is not a purely theoretical consideration, as processes are emerging for producing wires with a well-defined rectangular or square cross-section (Sergelius et al, 2014). Also, the latter should not be confused with the vortex wall in strips (McMichael and Donahue, 1997;Nakatani et al, 2005), which has a different shape and even topology, as we will detail later.…”
mentioning
confidence: 99%
“…Nowadays, the modulation in diameter imprinted along the length of magnetic nanowires has become as a promising route to tailor their magnetic properties, allowing for a controlled motion of magnetic domain walls (DWs) and the possibility to manipulate the DW displacement by applying magnetic fields for their implementation in new-generation devices for information storage, logic system and sensors [1][2][3][4][5][6][7][8]. Cylindrical nanowires with modulated diameter and specific compositions are fabricated by different techniques such as the combination of mild and hard anodization processes [9][10][11] or by anodization together with atomic layer deposition (ALD) technique [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we propose a design for a multilayered soliton shift register which only uses dipolar interaction and in-plane shape anisotropy. Such a device can be realized due to the recent progress in nanowires fabrication techniques [18][19][20][21][22][23] . This device also has the added advantage that it can be fabricated using more commercially competitive methods such as electro-deposition 21 and atomic layer deposition 19,20,22 , which are unlikely to produce interfaces of sufficient quality to support strong RKKY interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Such a device can be realized due to the recent progress in nanowires fabrication techniques [18][19][20][21][22][23] . This device also has the added advantage that it can be fabricated using more commercially competitive methods such as electro-deposition 21 and atomic layer deposition 19,20,22 , which are unlikely to produce interfaces of sufficient quality to support strong RKKY interactions. Sergelius et al have shown that by using laser interference lithography to create nanochannel arrays, rectangular bars with high aspect ratios and with lateral dimensions similar to the ones described in this manuscript can be fabricated experimentally 22 .…”
Section: Introductionmentioning
confidence: 99%